Disaster risk reduction for whom? The gap between centrally planned Disaster Management Program and people's risk perception and adaptation. (November 2022) - Haque, Ashraful; Fatema, Kaniz
Abstract: Integration of Disaster Risk Reduction (DRR) and Climate Change Adaptation (CCA) is gaining popularity to address the increasing threat of climate change. People living in high disaster-prone impoverished areas can benefit from risk reduction interventions and subsequent adaptation of new technologies and behavior if those interventions diminish the perceived risk of disaster. Perceived risk of disaster plays an important role in influencing adaptive behavior. Disaster risk reduction interventions therefore can be benefitted from inclusive local consultation during the planning and implementation of the risk reduction interventions by taking local people's perceived risk of disaster into account. We studied a national-level disaster risk reduction program called 'The comprehensive Disaster Management Program (CDMP)' in Bangladesh to understand the linkage between risk reduction interventions, perceived risk of disaster, and adaptation. Following a mixed-method approach, we collected quantitative administrative data, interviewed local people, and conducted Focus Group Discussions in two disaster-prone neighboring coastal unions of Bangladesh. We have found that if risk reduction interventions designed by the central government are not aligned with the perceived risk of the local people, the implementation of these interventions does not reduce perceived risk significantly, and consequently, people do not adopt new technologies and behavior to increase their resilience to climate change shocks. Furthermore, people's valuation of a risk reduction intervention in reducing the perceived risk of disasters does not change after an actual disaster takes place insinuating the relative accuracy and robustness of local people's assessment of such interventions. We also found that risk reduction interventions implemented in a holistic way addressing multiple sources of risks can reduce perceived risk significantly. Lastly, we demonstrated that reducing perceived risk is a necessary condition but is not sufficient to encourage adaptation. Our study can contribute to improving the design and implementation of large-scale risk-reduction interventions implemented at the community level. Highlights: If risk reduction interventions are not aligned with local people's assessment of these interventions in their potential to reduce the risk of disasters, implementation of such interventions does not reduce the perceived risk of disaster. Local people by living in an area for decades develop the capacity to assess risk reduction interventions' efficacy with relative accuracy and robustness as measured through their consistent risk assessment of such interventions before and after a disaster. Contrary to the prevailing theory on the risk-adaptation linkage, we found that reduced perceived risk can significantly increase adaptation by creating a sense of opportunity and control that makes future adaptation more attractive. Multiple risk reduction interventions addressing different sources of disaster risks are necessary to reduce perceived risk significantly. Perceived risk is a necessary condition but not sufficient to encourage adaptation.